Physicochemical characterisation of severely aged crumb rubber modified bitumen - Liu, Jiayao; Yang, Qian; Zhang, Yan; Wang, Shaokun; Wei, Wei; Su, Wenbin; Wu, Rui (Frontiers in Materials, 2025)
Crumb rubber was incorporated into neat bitumen at a dosage of 15 wt% to mitigate the challenges of rising crude oil prices, high dependence on fossil fuels, and energy shortages. Both the unmodified bitumen and crumb rubber modified bitumen (CRMB) were subjected to short- and severe long-term ageing. The rheological properties were evaluated using a dynamic shear rheometer (DSR) and a bending beam rheometer (BBR) to investigate the high-, intermediate-, and low-temperature performance of the binders under different ageing conditions. Fourier-transform infrared spectroscopy (FTIR) was employed to characterise the chemical changes with modification and ageing. The results indicate that the incorporation of crumb rubber significantly enhances the high- and low-temperature performance of bitumen but slightly reduces its fatigue resistance and durability. Crumb rubber does not alter the oxidation pathway of bitumen. After severe long-term ageing, the chemical characteristics of CRMB remain comparable to those of neat bitumen.